Katuk Leaf, Carrot, and Pineapple Mixed Juice: A New Media for the Non-dairy Probiotic Drink - Yuliana, Neti; Aulia, Trisna; Hanum, Tirza; Ranga, Azhari (Food Science and Engineering, 2025)
Mixed vegetable and fruit juices are promising for developing non-dairy probiotic beverages. This study investigated the physicochemical properties, sensory acceptance, and the viability of Lactobacillus casei 0090-NRRL B-1992 during refrigerated storage (4 °C) in a juice blend comprising Katuk (Sauropus androgynus) leaves, carrots, and pineapple. Four juice formulations with varying dilution ratios were prepared and evaluated over a 21-day storage period (0, 7, 14, and 21 days). Results indicated a gradual decline in both total Lactic Acid Bacteria (LAB) count and LAB viability percentage, as well as a decrease in total soluble solids throughout storage. Nevertheless, all treatments maintained LAB counts above the minimum threshold recommended for probiotic efficacy (≥ 106 CFU/mL). The total lactic acid content of the probiotic juices ranged from 0.19% to 1.36%, and this increase corresponded with a pH reduction from 4.81 to 3.41, reflecting enhanced LAB fermentative activity during cold storage. Sensory evaluation revealed an improvement in aroma and overall acceptability scores, particularly after 14 days of storage, from moderately liked to liked. Among the formulations, the 2 : 1 juice-to-water dilution ratio was most preferred and demonstrated potential as a candidate for further development as a probiotic mixed juice beverage.